2019
DOI: 10.3390/su11133529
|View full text |Cite
|
Sign up to set email alerts
|

Board Governance, Sustainable Innovation Capability and Corporate Expansion: Empirical Data from Private Listed Companies in China

Abstract: Within fierce market competition, economic integration acceleration, information technology development, customer demands that are more complex than ever before and product life cycle acceleration have greatly increased the complexity and uncertainty of the operating environment of Chinese private listed companies. Considering the special situation and the current situation of the enterprise development phase in China, the shaping and upgrading of sustainable innovation capability for Chinese private listed co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 73 publications
1
7
0
Order By: Relevance
“…The data used in the empirical analysis are all secondary data, mainly from CSMAR database, which is the primary source of information on Chinese stock markets and the financial statements of China's exchange-listed firms [41]. The sample and data collection steps are as follows: To begin with, based on the classification of group enterprises by Carney et al (2009) [42], the authors make A preliminary selection of samples for all A-share listed companies in Shanghai and Shenzhen Stock Exchanges [43]. Subsequently, the sample observation interval is defined as 2014-2018, and the companies marked ST or stopped to be listed during the observation period are excluded.…”
Section: Sample Selection and Data Sourcementioning
confidence: 99%
“…The data used in the empirical analysis are all secondary data, mainly from CSMAR database, which is the primary source of information on Chinese stock markets and the financial statements of China's exchange-listed firms [41]. The sample and data collection steps are as follows: To begin with, based on the classification of group enterprises by Carney et al (2009) [42], the authors make A preliminary selection of samples for all A-share listed companies in Shanghai and Shenzhen Stock Exchanges [43]. Subsequently, the sample observation interval is defined as 2014-2018, and the companies marked ST or stopped to be listed during the observation period are excluded.…”
Section: Sample Selection and Data Sourcementioning
confidence: 99%
“…The explanations concerning the dependent, independent and control variables of the research are given in Table 6. Xu and Bai (2019) Logarithm of the Total Assets TA…”
Section: Measurement Of the Research Variablesmentioning
confidence: 99%
“…Finally, using the data of certain private companies in China, Xu and Bai (2019) examined the relationship between board structure and sustainable innovation capability. The results indicated that the central leadership structure had a positive impact on the sustainable innovation capability of Chinese companies.…”
Section: Literaturementioning
confidence: 99%
“…The statement that received the highest score was S2.1. In their research, Xu and Bai [90] explain that managers in Chinese private companies tend to engage in maintaining a certain level of internal satisfaction, pursuing innovative decisions, improving the sustainable innovation of the company, and enhancing motivation and enthusiasm by encouraging innovation. However, statement S2.2 shows that this commitment does not always translate into action.…”
Section: Innovationmentioning
confidence: 99%